Resgatando o sentido do texto: contribuições da Teoria da Argumentação na Língua para a reconstrução do sentido de textos orais radiofônicos - Sena, Geane Cássia Alves (2012)
The main objective of this research is to show how the Theory of Argumentation in the Language (TAL) can cooperate with the rescue in the meaning of radiophonic oral texts by the reader/ listener. The radiophonic text, due to its ‘oral-audio’ style organizes itself quite differently from printed texts, because it’s built to be spoken and has only one chance to be heard. Therefore, it requires close attention of the reader, who besides being the listener, must be positioned in front of the radio text as a researcher who seeks, through the marks left by the interlocutor, rebuild the meaning of the text and not being a mere receiver or a ‘common reader’. Though it wasn’t meant for the development of reading and writing skills of texts, the Theory of Argumentation in the Language theoretical has rules that can be used during the process to assist in the rescue of the meaning of texts, as shown in this paper. In order to achieve our objective, we try to answer the following question: How can the Theory of Argumentation in Language help in the rescue of the meaning of radiophonic oral texts by its reader/ listener? To answer to that question, we sought for support in the studies about Rhetoric and in the Theory of Argumentation in the Language developed by authors such as Meyer (1994), Perelman and Olbrechts-Tyteca (1988), Tringali (1988), Ducrot (1987, 1988, 1989), Ducrot and Carel (2008), Cabral (2010), among others. We also based our answer in theories that discuss the radiophonic genres, the history of the radio in Brazil, the language and the building of radiophonic text such as Barbosa Filho (2009), Cabello (1994, 1995), Otriwano (1985), etc. The corpus consists of three radiophonic texts transcripts broadcast by Radio CBN (Central Brasileira de Notícias). The analysis procedures were based on some principles of the Theory of Argumentation in the Language, specially in the third phase of the theory, which were listed as procedures to be applied by the reader/ listener to the text, such as: the building of the semantic block, argumentative threads, argumentative aspects, connectors, text articulators and organizers, as well as the polyphonic analysis of statements from the Theory of Semantic Blocks. After the development of these analyses, we found that the Theory of Argumentation in the Language presents very useful foundations to the rescue in the meaning of the radiophonic oral texts, since it favors a more complex level of reading.